1987
DOI: 10.1111/j.1432-1033.1987.tb10734.x
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein Ib complex of human blood platelets

Abstract: Human glycoprotein Ib (GPIb) is a major integral membrane protein on human blood platelets responsible for the initial attachment of platelets to the exposed vascular subendothelium. In this report we describe an isolation method for a 'GPIb complex' as well as for its individual components. A three-step procedure involving Triton X-114 phase-partition, affinity chromatography on wheat germ agglutinin and ion-exchange chromatography on DEAE-Sephacel yielded milligram quantities of purified GPIb complex. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Of interest, AP1, VM16d, and TM60 all also inhibit thrombin-induced binding to GP Ib␣, [20][21][22][23] suggesting that this region contains an important thrombin binding site. This had been suggested previously by Katagiri et al,12 who showed that the peptide Phe216 to Thr240 inhibited high-affinity thrombin binding and by Wicki and Clemetson,24 who showed that an important thrombin binding site on GP Ib␣ lies N-terminal to Lys237. 21 This presumption has now been confirmed in 2 crystal structures of the GP Ib␣ N-terminus in complex with thrombin, which show this region of GP Ib␣ bound by thrombin exosite I.…”
Section: Introductionsupporting
confidence: 61%
“…Of interest, AP1, VM16d, and TM60 all also inhibit thrombin-induced binding to GP Ib␣, [20][21][22][23] suggesting that this region contains an important thrombin binding site. This had been suggested previously by Katagiri et al,12 who showed that the peptide Phe216 to Thr240 inhibited high-affinity thrombin binding and by Wicki and Clemetson,24 who showed that an important thrombin binding site on GP Ib␣ lies N-terminal to Lys237. 21 This presumption has now been confirmed in 2 crystal structures of the GP Ib␣ N-terminus in complex with thrombin, which show this region of GP Ib␣ bound by thrombin exosite I.…”
Section: Introductionsupporting
confidence: 61%
“…Glycocalicin can be split into a 90 kDa fragment and a 45 kDa fragment [18]. Carbohydrate analysis of these fragments (not shown) shows that the 90 kDa fragment contains almost exclusively O-linked and the 45 kDa fragment N-linked carbohydrate chains.…”
Section: Discussionmentioning
confidence: 99%
“…GPIb was purified from outdated platelet concentrates collected by the Belgian Red Cross in Leuven, Belgium, according to the method described by Wicki and Clemetson. 24 BALB/c mice were immunized by intraperitoneal injection with the purified GPIb. Murine antibodies were prepared by conventional hybridoma technology as previously described, 25 and generated hybridoma cells were screened for antibody production in an ELISA by using purified GPIb.…”
Section: Preparation and Purification Of Intact Moab 6b4 F(ab ) 2 mentioning
confidence: 99%